Cape Verde Expedition - Cruise No. M4 - October 3 - December 6, 1986 - Kiel (Germany) - Kiel (Germany) - Siedler, Gerold; Schmickler, Heino; Müller, Thomas J; Schenke, Hans-Werner; Zenk, Walter (DFG-Senatskommission für Ozeanographie, 1987)
The first part of METEOR cruise No. 4 between Kiel and Lisbon included a technical and scientific testing program. The aim was to test the new side-looking echosounder system HYDROSWEEP and the integrated navigation system INS. This report summarizes the activities and presents results of this project. The second part of the cruise from Lisbon via Sta. Cruz and Dakar to Kiel included a multidisciplinary research program in the Canary and Cape Verde Basins. The principal aim was to study the circulation and mixing in the eastern part of the North Atlantic subtropical gyre. In addition to the related physical and chemical measurements the following program was carried out: Sampling with sediment traps for the determination of the oceanic particle flux, air chemistry measurements for the oberservation of Sahara aerosol, and aerological measurements in the atmospheric boundary layer. The report summarizes the oberservational program, and tentative results are presented. : METEOR-Berichte